The relationship between infant iron status and risk of neurological impairment - Buntat Buntat; Nurhayati Masloman; Johnny Rompis (Indonesian Pediatric Society, 2017)
Background Iron deficiency (ID) is a commonly found nutritional disorder and a persistent problem, especially in Indonesia. Iron deficiency during the critical period in childhood brain development is estimated to cause irreversible damage that hinders infant development. Objective To determine the relationship between infant iron status and neurological development. Methods We conducted a cross-sectional study at the Growth and Development Outpatient Clinic, Prof. Dr. R. D. Kandou Hospital, Manado, from March to May 2015. By consecutive sampling, we obtained 44 healthy infants aged 7 to 10 months who fulfilled the inclusion criteria. Infants with a history of perinatal complications, such as head trauma, hypoglycemia, respiratory distress syndrome, infection, or malaria were excluded Subjects' serum hemoglobin and ferritin were examined for iron status. Infants' risk of neurological impairment was assessed by the Bayley Infant Neurodevelopmental Screener (BINS). Results were analyzed by descriptive analysis for the characteristics and Spearman's rank correlation coefficient analysis for the relationship between iron status and neurological development. Results From 14 infants with ID, 8 infants had a high risk of developmental impairment. Of the 30 non-ID subjects, 4 infants had a high risk of developmental impairment. Of the 30 non-ID infants, 16 infants had a low risk of impaired development, while 2 infants with ID had low risk of developmental impairment. Spearman's rho revealed that infant iron deficiency was significantly associated with high risk of neurological impairment. (r=-0.547; P<0.0001). Conclusion Lower serum ferritin levels (iron deficiency) is significantly associated with greater risk of impaired neurological development in infants aged 7-10 months.